Design and Implementation of an Integrated Digital Archive System for Supporting Academic Personnel Services - Muhammad Davi; Muhammad Reza Zulman; Muhammad Arhami (Universitas Malikussaleh, 2026)
Digital archive management in higher education institutions often faces challenges, including document fragmentation, inefficient retrieval, and data loss risks arising from semi-manual processes. This study aims to develop an integrated digital archive system to support personnel services for lecturers at Politeknik Negeri Lhokseumawe. The research employs APKL (Actual, Problematical, Public Concern, Feasibility) and USG (Urgency, Seriousness, Growth) methods for issue prioritization, followed by a Fishbone diagram for root cause analysis. The system was developed using a structured Software Development Life Cycle (SDLC) with a Human Resource Minimum Viable Product (HR MVP) approach. Evaluation via User Acceptance Testing (UAT) yielded an average score of 4.65 (Excellent category), indicating high user acceptance and system effectiveness. The implementation demonstrates that the system significantly improves document management efficiency, ensures data consistency, and accelerates personnel administrative services. This study concludes that the integrated digital archive system provides a robust, adaptive, and practical solution for enhancing administrative quality in higher education environments. Furthermore, the system incorporates intelligent software features, including automated document classification, proactive validation, and efficient search capabilities.